2012
DOI: 10.1603/me11202
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Bed Bug Populations Reveals Small Propagule Size Within Individual Infestations but High Genetic Diversity Across Infestations From the Eastern United States

Abstract: Bed bugs (Cimex lectularius L.) are a resurgent pest worldwide and infestations within the United States are increasing at a rapid rate. Because of the physical and psychological discomfort inflicted by their blood feeding habits, and allergies and secondary infections associated with bites, bed bugs are recognized as a significant public health problem. Although bed bug infestations are spreading and becoming more prevalent, we have a poor understanding of their dispersal patterns and sources of infestation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
88
3
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 56 publications
10
88
3
1
Order By: Relevance
“…All loci used in this study had unique alleles in addition to those previously identified by Saenz et al (2012) and Booth et al (2012). The possible explanation that fits this scenario is outbreeding and random mating by the female bed bugs.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…All loci used in this study had unique alleles in addition to those previously identified by Saenz et al (2012) and Booth et al (2012). The possible explanation that fits this scenario is outbreeding and random mating by the female bed bugs.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies by Booth et al (2012) and Saenz et al (2012) on the genetic diversity of bed bugs in the eastern United States demonstrated that microsatellite markers were a useful tool to differentiate bed bug populations within an apartment building or even across large areas (Massachusetts to Florida). Our report is the first analysis of bed bug populations in the Midwest, including Nebraska and Missouri.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People from all social and economic levels are affected by bed bugs, and bed bug infestations are found in almost every human-made structure, including hotels, apartments, hospitals, military camps, homeless shelters, office buildings and college dormitories (Potter et al, 2010). After the extensive application of organophosphate insecticides in the years following World War II, bed bug infestations were diminished; they were only rarely reported in industrialized countries after the 1950s (Snetsinger, 1997;Cooper, 2006;Harlan, 2006;Booth et al, 2012). However, since the mid-1990s, the reported number of human bed bug infestations has increased significantly, originally in North America, Western Europe and Brazil, and later in various countries in Eastern Europe (Pinto et al, 2007;Reinhardt and Siva-Jothy, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This movement may occur via furniture, clothing, used mattresses, suitcases and/or other personal possessions. Bugs may also migrate from one apartment or hotel room to another through holes in walls, water pipes, or gutters (Wang et al, 2010, Booth et al, 2012. Infestation dynamics and bed bug prevalence (C. lectularius) are important aspects of bed bug biology that have not been well studied in France.…”
Section: Introductionmentioning
confidence: 99%